2022
DOI: 10.1111/aepr.12377
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Digital Financial Inclusion in Emerging Market and Developing Economies: A New Index

Abstract: Adoption of technology in the financial services industry has been accelerating in recent years. To assess its contribution to financial inclusion, we develop a novel digital financial inclusion index covering 52 emerging market and developing economies. We find that (i) the adoption of digital financial services has been a key driver of financial inclusion; and (ii) there is wide variation across countries and regions, with the greatest progress recorded in Africa and Asia. Given the accelerated adoption of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
60
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 21 publications
0
60
2
1
Order By: Relevance
“…Khera et al (2022) provides a novel measurement of digital financial inclusion using a three‐stage principal component approach (PCA) for 52 emerging market and developing economies. Based on this new index, they have found that the adoption of digital financial services has been a key driver of financial inclusion, and countries/regions in Africa and Asia and regions have achieved greater progress.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Khera et al (2022) provides a novel measurement of digital financial inclusion using a three‐stage principal component approach (PCA) for 52 emerging market and developing economies. Based on this new index, they have found that the adoption of digital financial services has been a key driver of financial inclusion, and countries/regions in Africa and Asia and regions have achieved greater progress.…”
mentioning
confidence: 99%
“…Overall, this index has great potential for deepening our understanding of the relationships between comprehensive financial inclusion, digital financial inclusion as well as traditional financial inclusion. In this aspect, Khera et al (2022) may wish to provide more discussions so that the importance of subindices can be better appreciated. For example, Khera et al’s Figures 1 and 2 indicate that African countries excel in digital financial inclusion, so it would be insightful to explain which of the access and the usage components are relevant in promoting the development in digital financial inclusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To empirically examine digital‐based financial inclusion, Khera et al . (2022) develop a novel, comprehensive index of digital financial inclusion for 52 emerging and developing economies for 2014 and 2017. The index is constructed by combining the widely used cross‐country data on financial inclusion and related aspects.…”
mentioning
confidence: 99%
“…Morgan (2022) provides an overview of the development of financial inclusion and fintech in the Association of Southeast Asian Nations (ASEAN) region and India. This is complemented by Khera et al (2022) who provide estimates of a several new indices that enable us to see how digital financial inclusion and overall financial inclusion vary across emerging market and developing economies, and over time. Developments within central banks are discussed by Cornelli et al (2022) who focus on big data in Asian central banks, while Xu (2022) examines the development of China's digital currency (DC), the China e-CNY.…”
mentioning
confidence: 99%